Student Learning Motivation as Effort to Improve Learning Outcomes of Aqidah Akhlak in MIN 7 Southeast Aceh - Harli Harli (CV. Pusdikra Mitra Jaya, 2022)
The problem of decreasing learning outcomes is a question mark for teachers, parents and the school. For this reason, it is necessary to have strong motivation so that students continue to be able to improve learning outcomes in accordance with predetermined standard results. This research uses qualitative data analysis with field study techniques, documentation and interviews. At the data analysis stage using data reduction, data presentation, drawing conclusions. To determine the validity of the data, the criteria used are the degree of trust (credibility), transferability (transferability), dependability (dependability), and certainty). The results of the study indicate that there is a need for effectiveness in the learning process so that learning is right on target according to the curriculum that should be, there is self-evaluation carried out on students, teachers and parents and culture to provide motivation for students in each lesson.